Neighbourhood characteristics and the incidence of first-episode psychosis and duration of untreated psychosis. Issue 7 (5th February 2016) - O'Donoghue, B.; Lyne, J. P.; Renwick, L.; Lane, A.; Madigan, K.; Staines, A.; O'Callaghan, E.; Clarke, M.
Abstract : Background: The incidence of psychotic disorders varies between geographical areas and it has been hypothesized that neighbourhood-level factors may influence this variation. It is also plausible that the duration of untreated psychosis (DUP) is associated with neighbourhood characteristics. The aims of this study were to determine whether the incidence of first-episode psychosis (FEP) and the DUP are associated with the level of social deprivation, fragmentation, social capital and population density. Method: All individuals with a FEP from a geographical defined catchment area over a 5-year period were included. Age-standardized incidence rates were calculated for each neighbourhood factor. Results: A total of 292 cases of FEP were included in the study and 45% had a diagnosis of a schizophrenia-spectrum disorder. The age standardized incidence rate of FEP in the most deprived area was 72.4 [95% confidence interval (CI) 26.4–162.7] per 100 000 person-years compared with 21.5 (95% CI 17.6–26.0) per 100 000 person-years in the most affluent areas. This represents a 3.4-fold increase in FEP incidence in the most deprived areas. The incidence of FEP was also increased in neighbourhoods that were more socially fragmented [incidence rate ratio (IRR) = 2.40, 95% CI 1.05–5.51, p = 0.04] and there was a trend for the incidence to be increased in neighbourhoods with lower social capital (IRR = 1.43, 95% CI 0.99–2.06, p = 0.05). The median DUP was 4 months and was higher in more socially fragmented neighbourhoods. Conclusions: The incidence of psychotic disorders is related to neighbourhood factors and it may be useful to consider neighbourhood factors when allocating resources for early intervention services.